2008
DOI: 10.1111/j.1750-2659.2008.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

A vaccine manufacturer’s approach to address medical needs related to seasonal and pandemic influenza viruses

Abstract: Vaccination is considered to be one of the most effective tools to decrease morbidity as well as mortality caused by influenza viruses.For the prevention of seasonal influenza, Fluarix™ and FluLaval™ have been marketed since 1987 and 1992, respectively. Both vaccines have consistently been shown to meet or exceed the regulatory criteria for immunogenicity against the three strains H1N1, H3N2 and B, have a good safety profile, and are recommended for vaccinating children and adults of all ages.For the preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 40 publications
(115 reference statements)
0
27
0
1
Order By: Relevance
“…After using the vaccine on a larger scale, adverse events surveillance programs in the United States of America and China showed similar results (CDC 2009b, Wu et al 2010, Liang et al 2011. The other vaccine used in the campaign, a split-virus AS03-adjuvanted vaccine, was based on pre-pandemic vaccines against influenza A (H5N1), which had a more restricted clinical use (Baras et al 2008, Girard et al 2010. The studies evaluating the influenza H5N1 vaccine containing the adjuvant AS03 have associated its presence with an increase in vaccine reactogenicity (Leroux-Roels et al 2007, Baras et al 2008, Rümke et al 2008) and trials conducted with the AS03-adjuvanted H1N1 pandemic vaccine also found high rates of adverse events.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…After using the vaccine on a larger scale, adverse events surveillance programs in the United States of America and China showed similar results (CDC 2009b, Wu et al 2010, Liang et al 2011. The other vaccine used in the campaign, a split-virus AS03-adjuvanted vaccine, was based on pre-pandemic vaccines against influenza A (H5N1), which had a more restricted clinical use (Baras et al 2008, Girard et al 2010. The studies evaluating the influenza H5N1 vaccine containing the adjuvant AS03 have associated its presence with an increase in vaccine reactogenicity (Leroux-Roels et al 2007, Baras et al 2008, Rümke et al 2008) and trials conducted with the AS03-adjuvanted H1N1 pandemic vaccine also found high rates of adverse events.…”
Section: Discussionmentioning
confidence: 61%
“…The other vaccine used in the campaign, a split-virus AS03-adjuvanted vaccine, was based on pre-pandemic vaccines against influenza A (H5N1), which had a more restricted clinical use (Baras et al 2008, Girard et al 2010. The studies evaluating the influenza H5N1 vaccine containing the adjuvant AS03 have associated its presence with an increase in vaccine reactogenicity (Leroux-Roels et al 2007, Baras et al 2008, Rümke et al 2008) and trials conducted with the AS03-adjuvanted H1N1 pandemic vaccine also found high rates of adverse events. Local mild to moderate reactions were more common and serious adverse events were rarely reported (Carmona et al 2010, Roman et al 2010a, b, Waddington et al 2010, Nicholson et al 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…95 The current question is how to produce an effective pandemic influenza vaccine. 96,97 Focusing on classical influenza, the problem of the genetic shift highlights the problem of the efficacy of the in-use influenza vaccine. In the case of the novel influenza swine flu, the problem remains.…”
Section: Concepts On Finding New Vaccine For Swine Flumentioning
confidence: 99%
“…[51][52][53] GSK's vaccine pricing has accounted for and taken advantage of its broad vaccine portfolio. GSK has offered volume discounts and price bundling (i.e., discounts if different vaccine products are purchased together) to encourage payers to purchase across its portfolio.…”
mentioning
confidence: 99%